Development of Manually-Operated Groundnut Roasting Machine - Idris Adekunle Lateef; Oluyomi Johnson Oyeniran; Babatunde Adegbola Hassan; Adeniyi Adelekun; Samson Olusegun Fatukasi (ABUAD Journal of Engineering Research and Development)
Groundnut (Arachis hypogea) is one of agricultural product that has wide range of usage to man, animal and industries.  It is consume both raw and fried by man and animal, serve as a source of income and a raw material for industries. Groundnut required roasting process to generate oil, bring out characteristic aroma, flavour and a times an acceptable colour for its consumption. In a developing country like Nigeria, this process is done locally. the local method associated with problems and difficulties which make it ineffective, laborious and time consuming, therefore there is need for another improved   method. A manually operated Groundnut seed roaster was constructed with the aim of improving on the local methods. It contain Roast chamber, the pulley (which serve as Flywheel) shaft (Agitator), the heating unit (Gas burner and its accessory) and the discharge outlet. The machine after testing shows the frying efficiency of 88.125% with percentages of seed damaged (loss) to be 23.75%. The average and optimum time for roasting was estimated to be in the range of 6 minutes. The machine is  inch free and can be operated freely, hence recommended for use.